A study on antibiotic resistance pattern among patients of a selected hospital in Narayanganj, Bangladesh - Khan, Shahin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2024.